Redistribution of Calving Caribou in Response to Oil Field Development on the Arctic Slope of Alaska - Cameron, Raymond D.; Reed, Daniel J.; Dau, James R.; Smith, Walter T. (ARCTIC, 1992)
Aerial surveys were conducted annually in June 1978-87 near Prudhoe Bay, Alaska, to determine changes in the distribution of calving caribou (Rangifer tarandus granti) that accompanied petroleum-related development. With construction of an oil field access road through a calving concentration area, mean caribou density (no./sq. km) decreased from 1.41 to 0.31 (P=0.05) with 1 km and increased from 1.41 to 4.53 (P=0.04) 5-6 km from the road. Concurrently, relative caribou use of the adjacent area declined (P<0.02), apparently in response to increasing surface development. We suggest that perturbed distribution associated with roads reduced the capacity of the nearby area to sustain parturient females and that insufficient spacing of roads may have depressed overall calving activity. Use of traditional calving grounds and of certain areas therein appears to favor calf survival, principally through lower predation risk and improved foraging conditions. Given the possible loss of those habitats through displacement and the crucial importance of the reproductive process, a cautious approach to petroleum development on the Arctic Slope is warranted.Key words: Alaska, calving, caribou, disturbance, oil field RÉSUMÉ. Des photographies aériennes ont été prises au mois de juin chaque année de 1978 à 1987 près de la baie Prudhoe en Alaska, en vue de déterminer les changements dans la distribution des caribous (Rangifer tarandus granti) qui mettaient bas, changements accompagnant les projets de mise en valeur reliés au pétrole. Avec la construction d’une route d’accès à un champ pétrolifère à travers une zone importante de mise bas, la densité moyenne du caribou (nombre d’individus/km2) diminuait de 1,41 à 0,31 (P = 0,OS) à moins d’1 km de la route et augmentait de 1,41 à 4,53 (P = 0,04) à une distance de 516 km de la route. En même temps, l’utilisation relative de la zone adjacente par le caribou diminuait (P < 0,02), apparemment enréponse à l’augmentation de la mise en valeur de surface. On suggère que la ...